Social networks and aggressive attitudes: who is who. Scoping review of the scientific production on their relationships - Martín-Martín, Margarita; Bueno-Álvarez, José Antonio (Frontiers in Psychology, 2023)
Introduction. In the current world, an increasing number of people use social networks as a scenario for socialization, which have come to stay as a part of human development. During this socialisation process, violent situations occur all too often, despite their virtuality, and seriously compromises the emotional well-being of the other participants. Based on the work conducted on this subject, the following systematic review aims to establish the state of the art regarding the relationship between moral disengagement, disruptive behaviour and emotional intelligence of social network users. Method. A scoping review is carried out, according to the PRISMA-ScR criteria, consulting the WoS, Scopus, Education database, PsycINFO, PsycARTICLES, PLOS one and ScienceDirect databases, from 2021 up to the present day. Results. A total of 999 articles related to the research topic were collected, although the result of research responding to the specific search criteria was reduced to 10. Discussion. The research identified shows that there is a relationship between the level of moral development of social network users and their participation in aggressive online behavior. However, more research is needed, as it has not been demonstrated whether it is the networks that develop or favour the emergence of these attitudes, or simply act as facilitators for their amplified expression.